Construction methods and retrofitting techniques of selected heritage structures in Cebu - Ecarma, Clarice B.; Germar, Fernando J. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
The Philippines is regularly subjected to various hazards such as earthquakes and typhoons, causing damage to properties such as heritage structures. The construction method and materials used for these structures are often drastically unlikely to survive against the threat of the present day's various hazards. The main objective of this study is to recommend retrofitting techniques for the structures by: (i) identifying and comparing construction materials, methods and technology used for the structures and (ii) assessing the seismic vulnerability of the structures through qualitative analysis. Three structures in Cebu were selected to be investigated. Common modes of failure were identified through qualitative analysis. From the investigation, it was observed that the common failure mechanism likely to happen to the structures are stress concentrations, overturning or toppling, connection failures and delamination. These failure modes typically depend on the construction methods and materials used to the structures. Selection of retrofitting techniques to address each modes of failure was done by the researcher's evaluation through literature review. Evaluation and comparison of these retrofitting techniques were done which involves different aspects such as buildability, economy, overall structural performance and historical integrity. Applying reinforcements on the openings, grout injection or re-pointing on the masonry units, external polypropylene mesh on the corners and anchoring the walls are the most feasible retrofitting techniques for the structures to address different modes of failure. A balance of economy, safety, and historical integrity should be considered in selecting retrofitting techniques.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Historic buildings -- Earthquake effects; Historic buildings -- Conservation and restoration; Church buildings -- Philippines -- Cebu (Province)